Sensitivity and Specificity of BMI and Abdominal Circumference as Indicators of Diabetes Risks - Yosi Irene Putri (Jurnal Kesehatan Medika Saintika, 2018)
Background: Increased prevalence of obesity has an impact on increasing the risk of diabetes mellitus. BMI (Body Mass Index) and abdominal circumference are measure to assess a person including obesity or not and  the best indicator in determining the risk of developing diabetes. Objective: This study aims to assess sensitivity and specificity of BMI and abdominal circumference as an indicator of diabetes risk and using Receiver Operator Characteristic Curve (ROC). Design: The design of this study was observational (cross sectional). The data used are secondary data from the results of research metabolic syndrome on adults at Health Laboratory Hall, West Sumatera Province in 2014, with 58 people. inclusion criteria aged 30-60 years, blood glucose examination and exclusion criteria of pregnant women. Results: Shows that the average of BMI are 25,18 kg/m2. The test of sensitivity and specificity of BMI as both an indicator of diabetes risk was > 25 kg/m2 (Se 87% and Sp 76%) whereas, in both abdominal circumference as an indicator of diabetes risk was 90 cm in men and 80 in women (Se 91% Sp 58%). Analysis with ROC showed that the optimum sensitivity and specificity combination (> 0.8) was at 25.6 kg/m2 BMI with Se 87% and Sp 83% for diabetes risk. Conclusions: abdominal circumference is better than BMI when used as an indicator of diabetes risk. Anthropometric measurements of height, weight and abdominal circumference can be done regularly and periodically to detect the occurrence of metabolic syndrome or the risk of diabetes.